(untitled) (University Heart Journal, 2012)
Coarctation of the aorta is a relatively common defect that accounts for 5-8% of all congenital heart defects. Coarctation of the aorta may occur as an isolated defect or in association with various other lesions, most commonly patent ductus arteriosus, bicuspid aortic valve and ventricular septal defect. The diagnosis of coarctation of the aorta may be missed or delayed unless there is a high index of suspicion and the presentation may be congestive heart failure in infant or hypertension in older children and adult. A case of coarctation of the aorta associated with patent ductus arteriosus having features of headache, exertional dyspnea and uncontrolled hypertension is being presented here. PTFE patch aortoplasty and ligation with transfixation of PDA was done. Post-operative period was uneventful and patient was discharged on 7th post-operative day. DOI: http://dx.doi.org/10.3329/uhj.v8i1.11671 University Heart Journal Vol. 8, No. 1, January 2012